SISTEM KEAMANAN MENGEMUDI KENDARAAN BERBASIS ARDUINO UNTUK MEMONITORING JARAK SEBUAH BENDA - Hermawan, Rinaldi; Rosiska, Evan (LPPM Universitas Putera Batam, 2021)
The development and advancement of technology at this time is very fast and has been implemented in many fields, starting from designing hardware (network networks, production machines, automotife, etc.), even software development (programming languages ​​and applications). One example of technological development which is currently developing rapidly is information technology. The desire of the user in realizing technology that is easy and understandable by humans is manifested in technology that is easy to understand to interact with a machine. The use of microcontrollers in the field of control and monitoring is already very popular in the surrounding community and is increasingly in the interest of several groups and helps in providing important information as well as helping the work to be carried out. The microcontroller is the most important part for processing and processing data in the work system. An example of the development of the Arduino uno microcontroller. Arduino uno is a device that provides various information services ranging from games, office jobs, audio-video. This study discusses the Arduino-based vehicle driving safety system for monitoring the distance of an object equipped with the HC-SR04 ultrasonic sensor installed on the vehicle, then as a processor the Arduino Uno microcontroller is used, as a security system used by Buzzer. which will send a message or notification in the form of a sound if the distance is too close. The function of this research is like reading distance and providing security in the form of sound.